Opiate Drug Consumption Patterns In Asia- Report Of A Regional Workshop. - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1981)
The Regional Workshop on Opiate Drug Consumption in Asia was a collaborative activity developed as part of the bilateral program for drug abuse control activities initiated by the 1978 Memorandum of Understanding signed between the Governments of the United States of America and Malaysia